The interaction between voice disorders and stress for work ability of teachers - Vertanen-Greis Hanna; Löyttyniemi Eliisa; Uitti Jukka; Putus Tuula (TAYLOR & FRANCIS LTD, 2022)
Objective
Less attention has been paid to the interaction between voice disorders, stress, and indoor environmental quality for work ability in teachers. Therefore, our aim was to study whether lower work ability associated more strongly when the variables of voice disorders and stress at work were combined as opposed to evaluating these two factors separately.
Methods
We conducted a questionnaire study including validated self-assessment of work ability and a technical assessment of school buildings utilizing a sample of 1198 and a subsample (n = 538) of Finnish teachers.
Results
When combined, voice disorders and stress at work had a stronger association to decreased work ability than when they were evaluated separately. The occurrence of stress was more prevalent in poor and moderate work ability than the occurrence of voice disorders. Nine out of 10 of the teachers who had neither voice disorders nor stress reported good work ability, while four out of 10 of the teachers who suffered from both voice disorders and stress had poor work ability. As regards the background variables, nearly half of the subjects working in the non-problem buildings have neither stress nor voice disorders.
Discussion
We recommend offering support for reducing stress at work to improve teachers’ work performance. The findings also support the maintenance of school buildings and keeping them in good condition. Follow-up studies are needed to investigate the possible effects of voice disorders and the associated variables on work ability